A method for producing substituted aromatics by alkylation, a catalyst and a preparation method thereof
By introducing cavity with specific size distribution inside the crystals of the molecular sieve catalyst, the problem of long diffusion path of the existing catalyst is solved, the activity, selectivity and stability of the catalyst are improved, and it is suitable for industrial alkylation reactions, achieving efficient preparation of ethylbenzene.
Patent Information
- Application Number
- CN202111138689.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-09-27
AI Technical Summary
The existing alkylation catalysts have long diffusion paths during the reaction, resulting in reduced activity, decreased selectivity and shortened lifetime. The catalyst has low bulk density and low loading volume, which affects industrial applications.
By introducing three size distributions of nearly spherical cavity inside the crystals of the molecular sieve catalyst, the diameter distribution range is 5-35nm, 40-55nm and 60-100nm, the structure and composition of the catalyst are optimized and its activity, selectivity and stability are improved.
It effectively solves the problem of long diffusion paths, improves the diffusion rate of the reaction molecules and the activity, selectivity and stability of the catalyst, is suitable for industrial benzene alkylation reactions, and improves the conversion rate and ethyl selectivity of ethylbenzene.
Smart Images

Figure CN115845913B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic chemistry and chemical engineering, and in particular relates to a method for producing aromatic hydrocarbons by alkylation, a catalyst thereof, and a method for preparing the catalyst. Background Art
[0002] Substituted aromatics are important basic organic raw materials with a wide range of uses and play a vital role in the development of the national economy.
[0003] Substituted aromatics can be obtained through alkylation reactions, for example, alkylation of benzene and ethylene can obtain ethylbenzene, alkylation of benzene and propylene can obtain isopropylbenzene, alkylation of benzene and butene can obtain butylbenzene, alkylation of ethylbenzene and ethylene can obtain diethylbenzene or triethylbenzene, alkylation of ethylbenzene and propylene can obtain ethylisopropylbenzene, alkylation of isopropylbenzene and propylene can obtain diisopropylbenzene or triisopropylbenzene, alkylation of toluene and ethylene can obtain methylethylbenzene, alkylation of toluene and propylene can obtain methylpropylbenzene, alkylation of ethylene and tert-butylbenzene can obtain ethyltert-butylbenzene, alkylation of toluene and isobutylene can obtain methyltert-butylbenzene, alkylation of ethylbenzene and isobutylene can obtain ethyltert-butylbenzene, and so on.
[0004] The key technology of alkylation to substituted aromatics is to develop catalysts with high activity, high selectivity and high stability. The effective component of the catalyst is molecular sieve, which has a pure microporous structure. In the actual reaction process, there are problems such as long diffusion path and slow diffusion rate, which will lead to reduced activity, reduced selectivity and shortened life of the catalyst. Introducing cavities inside the microporous molecular sieve can effectively shorten the diffusion path of the reaction molecules, increase the diffusion rate of the reaction molecules, and the generated target products can also quickly diffuse out of the reaction system to avoid side reactions. It can also effectively inhibit the generation of heavy components and slow down the rate of carbon deposition, thereby greatly improving the activity, selectivity and stability of the catalyst.
[0005] CN 201811515890.4 discloses a hollow multi-level pore Beta molecular sieve and a preparation method thereof, mainly comprising the following steps: S1, dissolving a double-headed quaternary ammonium salt surfactant N2-p-N2, sodium hydroxide, and sodium metaaluminate in a mixed solution of water and anhydrous ethanol, stirring and mixing to obtain a mixed solution; S2, dripping ethyl orthosilicate into the mixed solution obtained in step S1 under stirring conditions, and continuing to stir until a gel solution is formed; S3, transferring the gel solution obtained in step S2 to an autoclave for hydrothermal crystallization, washing and filtering with water after crystallization, and then vacuum drying; S4, placing the dried product of step S3 in a muffle furnace for roasting to obtain a hollow multi-level pore Beta molecular sieve. The method uses a cut double quaternary amphiphilic small molecule to hydrothermally synthesize a hollow multi-level pore Beta molecular sieve in one step. The hollow multi-level pore Beta molecular sieve prepared by this method has a large hollow cavity and a thin mesopore wall. The molecular sieve is very easy to break in the actual industrial application process. In addition, the molecular sieve is used as a catalyst, and its bulk density is low, resulting in a small amount of catalyst loading. If used in an industrial device, the reaction performance will be greatly reduced. In addition, the structure of the diquaternary ammonium head amphiphilic molecular template agent used in this method is quite complex, expensive and difficult to obtain, which is extremely unfavorable for large-scale industrial application.
[0006] In summary, if further technological innovation is achieved to prepare molecular sieve catalysts with specific morphology and specific proportions of combined cavities, then the above-mentioned multiple problems can be solved at the same time, which will definitely greatly improve the activity, selectivity and stability of the catalyst. Summary of the invention
[0007] The present invention aims to provide a method for producing substituted aromatics by alkylation, so as to further improve the efficiency of the alkylation reaction, especially to improve the conversion rate of the raw materials, the selectivity of the products and the stability of the catalyst.
[0008] The first aspect of the present invention is to provide a method for producing substituted aromatics by alkylation, wherein the raw aromatics and olefins are contacted with a molecular sieve catalyst to react to generate substituted aromatics; the molecular sieve crystals in the molecular sieve catalyst contain three kinds of nearly spherical cavities with size distributions, and the diameter distribution ranges of the circles corresponding to the vertical projections of the three cavities from top to bottom are within 5-35nm, 40-55nm and 60-100nm respectively.
[0009] In the above technical solution, preferably, the proportions of the three types of cavities are 15-45%, 45-75% and 5-10% respectively.
[0010] In the above technical solution, preferably, the reaction temperature is 50-260°C, the reaction pressure is 0.1-5.0 MPa, and the olefin mass space velocity is 0.1-20.0 h -1, the molar ratio of aromatics to olefins is 1-30.
[0011] In the above technical solution, preferably, the aromatic hydrocarbon is one or more of benzene, toluene, ethylbenzene, n-propylbenzene, isopropylbenzene, n-butylbenzene, isobutylbenzene and tert-butylbenzene.
[0012] In the above technical solution, preferably, the olefin is one or more of ethylene, propylene, n-butene and isobutylene. The olefin may be a single component, multiple components, or other mixtures containing the above olefins.
[0013] In the above technical solution, preferably, the substituted aromatic hydrocarbon is any product or a mixture thereof generated by the reaction of the aromatic hydrocarbon and olefin.
[0014] The second aspect of the present invention is to provide a catalyst for producing substituted aromatics by alkylation, wherein the catalyst is a molecular sieve catalyst, wherein the interior of the molecular sieve crystals in the catalyst contains nearly spherical cavities of three size distributions, and the diameter distribution ranges of the circles corresponding to the vertical projections of the three cavities from top to bottom are respectively within 5-35nm, 40-55nm and 60-100nm.
[0015] In the above technical solution, preferably, the proportions of the three types of cavities are 15-45%, 45-75% and 5-10% respectively.
[0016] In the above technical solution, preferably, the molecular sieve is a silica-alumina molecular sieve having a twelve-membered ring pore structure, and more preferably a Beta molecular sieve.
[0017] In the above technical solution, preferably, the silicon-aluminum molecular sieve is a binder-free molecular sieve.
[0018] In the above technical solution, preferably, the total specific surface area of the catalyst is 680-950m 2 ·g -1 ; Total pore volume is 0.8-1.3cm 3 ·g -1 ; Mechanical strength is 70-100N / cm; Bulk density is 0.50-0.60g·cm -3 .
[0019] In the above technical solution, preferably, the SiO2 / Al2O3 molar ratio of the catalyst is 10-100.
[0020] The third aspect of the present invention is to provide a method for preparing a catalyst for producing substituted aromatics by alkylation, comprising the following steps:
[0021] (a) treating the molecular sieve with an acid and an ammonium salt solution to obtain a mixture E;
[0022] (b) The mixture E is contacted with a mixed organic base to obtain a mixture F, and the mixture F is treated at 120-170° C. for 24-96 hours, and then washed, dried, and calcined to obtain a molecular sieve catalyst.
[0023] In the above technical solution, preferably, the acid used for the acid treatment in step (a) is one or more of hydrochloric acid, sulfuric acid, and nitric acid, and the acid used for the acid treatment is an aqueous solution of the acid with a mass concentration of 0.1-1.0%.
[0024] In the above technical solution, preferably, in step (a), the ammonium salt is one or more of ammonium chloride, ammonium nitrate and ammonium sulfate, and the ammonium salt solution is an aqueous solution with a mass concentration of 3-30%.
[0025] In the above technical solution, preferably, the acid treatment condition in step (a) is 20-50° C. for 1-2 hours. The acid treatment is preferably carried out in a closed space.
[0026] In the above technical solution, preferably, the ammonium salt solution treatment condition in step (a) is 20-50° C. for 1-2 hours. Preferably, the ammonium salt solution treatment is carried out in a closed space.
[0027] In the above technical solution, preferably, the acid treatment or ammonium salt solution treatment is followed by washing and drying. The washing and drying can be carried out by conventional methods. For example, washing can be carried out by washing with deionized water until the pH value of the solution is 7-7.5. The drying conditions can be as follows: the drying temperature is 120-200°C and the drying time is 10-24 hours.
[0028] In the above technical solution, preferably, the weight ratio of the acid solution used for the acid treatment in step (a) to the molecular sieve is (1.2-20):1.
[0029] In the above technical solution, preferably, the weight ratio of the ammonium salt solution and the molecular sieve used in the ammonium salt solution treatment in step (a) is (1.2-20):1.
[0030] In the above technical solution, preferably, the mixed organic base in step (b) is a mixed organic base aqueous solution with a mass concentration of 8%-25%; the mass ratio of the mixed organic base aqueous solution to the mixture E is (1.2-15):1.
[0031] In the above technical solution, preferably, the mixed organic base described in step (b) is a mixed alkali aqueous solution of tetraethylammonium hydroxide and at least two other different quaternary ammonium bases, and the other quaternary ammonium bases have the structural formula:
[0032]
[0033] Wherein R1, R2, R3 and R4 are each independently selected from n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, benzyl or phenethyl. Wherein, R1, R2, R3 and R4 may be the same or different.
[0034] In the above technical solution, preferably, the mass ratio of tetraethylammonium hydroxide to the total amount of other quaternary ammonium bases is (5-8):1.
[0035] In the above technical solution, preferably, the mass proportion of each quaternary ammonium base in other quaternary ammonium bases is 20%-60%.
[0036] In the above technical solution, preferably, the washing, drying and roasting in step (b) can be carried out by any conventional method. For example, washing is carried out by washing with deionized water until the pH value of the solution is 7-7.5; the drying conditions can be as follows: the drying temperature is 120-200°C and the drying time is 10-24 hours; the roasting conditions can be as follows: the roasting temperature is 500-600°C and the roasting time is 5-10 hours.
[0037] In the above technical solution, the molecular sieve is preferably a binder-free molecular sieve.
[0038] In the above technical solution, the binder-free molecular sieve preparation process preferably comprises the following steps:
[0039] (1) contacting a first template, a silicon source, a first aluminum source, and water to obtain a mixture A;
[0040] The molar ratios of the first template, silicon source, first aluminum source and water are respectively: first template: silicon source = (0.15-0.65): 1; silicon source: first aluminum source = (10-100): 1, water: silicon source = (8-18): 1, wherein the silicon source is calculated as SiO2, and the first aluminum source is calculated as Al2O3;
[0041] (2) contacting mixture A, silicon powder and a second aluminum source to obtain mixture B;
[0042] The ratios of the mixture A, silicon powder and the second aluminum source are as follows: the weight ratio of the mixture A to the silicon powder is (0.5-1.2):1; the molar ratio of the silicon powder to the second aluminum source is (10-100):1; the silicon powder is calculated as SiO2, and the second aluminum source is calculated as Al2O3;
[0043] (3) forming the mixture B to obtain a mixture C;
[0044] (4) contacting the mixture C, the fluoride and the second template to obtain a mixture D, and washing, drying and calcining the mixture D to obtain a binder-free molecular sieve;
[0045] The weight ratio of the fluoride to the mixture C is (0.01-0.05):1, and the weight ratio of the second template to the mixture C is (1.2-3.5):1.
[0046] In the above technical scheme, preferably, the first template described in step (1) is tetraethylammonium hydroxide; the silicon source is one or more of water glass, silica sol, white carbon black, and tetraethyl silicate; the first aluminum source is one or more of sodium aluminate, pseudo-boehmite, aluminum chloride, aluminum nitrate, and aluminum sulfate, and more preferably, the first aluminum source is one or more of sodium aluminate and pseudo-boehmite.
[0047] In the above technical scheme, preferably, in step (1), the process of obtaining mixture A by contacting the first template, the silicon source, the first aluminum source and water is: stirring the first template, the silicon source, the first aluminum source and water in a closed container, the stirring time is 4h-15h, and the stirring temperature is 120-180°C.
[0048] In the above technical solution, preferably, the silicon powder in step (2) is silicon dioxide with a size distribution of 5-10 μm; the second aluminum source is a mixture of sodium aluminate and pseudo-boehmite, and the molar ratio of sodium aluminate and pseudo-boehmite is (0.8-2.2):1, calculated as Al2O3.
[0049] In the above technical solution, preferably, in step (3), mixture B is formed to obtain mixture C. Mixture C can be made into strips as needed, and its cross-section is circular, gear-shaped, clover-shaped, four-leaf clover-shaped or honeycomb-shaped. The diameter of mixture C is 1.0-4.0 mm and the length is 1-10 mm.
[0050] In the above technical solution, preferably, the fluoride in step (4) is one or more of ammonium fluoride, ammonium fluorosilicate, and hydrofluoric acid, and the second template is tetraethylammonium hydroxide;
[0051] In the above technical solution, preferably, in step (4), the process of contacting the mixture C, the fluoride and the second template to obtain the mixture D is: treating the mixture C, the fluoride and the second template in a closed space at 120-180° C. for 48-96 hours, and then washing, drying and calcining to remove organic matter.
[0052] In the above technical scheme, the washing, drying and roasting can be carried out by conventional methods. For example, the washing can be carried out with deionized water until the pH value of the solution is 7-7.5; for example, the drying conditions can be as follows: the drying temperature is 120-200°C and the drying time is 10-24 hours; the roasting conditions can be as follows: the roasting temperature is 500-600°C and the roasting time is 5-10 hours.
[0053] The method and catalyst for producing substituted aromatics by alkylation of the present invention have the following beneficial effects:
[0054] 1. It has been found through research that diffusion performance plays a vital role in benzene alkylation catalysts. For molecular sieve catalysts, if the molecular sieve crystals contain cavities of suitable size and proportion, the internal diffusion problem in the alkylation reaction process can be effectively solved, the diffusion rate of the reaction molecules can be increased, and the conversion rate can be effectively improved. In addition, the generated target product can quickly diffuse out of the reaction system, inhibit the occurrence of side reactions, and improve the selectivity of the target product. At the same time, the rate of carbon deposition can be slowed down and the service life of the catalyst can be increased. The molecular sieve crystals in the catalyst used in the method of the present invention contain cavities of specific size distribution and have a specific proportional relationship, which is particularly suitable for benzene alkylation reactions.
[0055] 2. The catalyst used in the method of the present invention is preferably a binder-free catalyst, which does not contain any inert components, completely eliminating the negative effects of the inert components on the dilution of the active components of the molecular sieve and the clogging of the micropores of the molecular sieve, and further improving the activity, selectivity and stability of the catalyst in the alkylation reaction process of ethylbenzene.
[0056] 3. The catalyst used in the method of the present invention has the characteristics of high specific surface area, high pore volume, high mechanical strength and suitable bulk density, and is particularly suitable for industrial benzene alkylation reaction devices. In addition, the mixed organic base used in the present invention is cheap and easy to obtain, and is suitable for large-scale industrial production.
[0057] 4. When the method of the present invention is used for the alkylation reaction of benzene and ethylene to produce ethylbenzene, under the reaction conditions of high ethylene mass space velocity and low benzene to ethylene molar ratio, the ethylene conversion rate is greater than 99.9% and the ethyl selectivity in the alkylation product is greater than 99.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 The XRD spectrum of the catalyst for producing aromatic hydrocarbons by alkylation prepared in Example 1 of the present invention;
[0059] Figure 2 This is a TEM photo of the alkylation catalyst for producing aromatics prepared in Example 1 of the present invention;
[0060] Figure 3 This is a TEM photo of the catalyst prepared in Comparative Example 1 of the present invention;
[0061] Figure 4 The XRD spectrum of the catalyst prepared in Comparative Example 2 of the present invention;
[0062] Figure 5 This is a TEM photograph of the catalyst prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0063] The present invention is described in detail below in conjunction with specific implementation modes, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.
[0064] The cavity size and distribution of the catalyst for producing aromatic hydrocarbons by alkylation in the present invention are obtained by analyzing TEM photos; the total specific surface area and total pore volume are obtained by nitrogen adsorption and desorption test; the mechanical strength is obtained by using an intelligent particle strength tester; and the SiO2 / Al2O3 molar ratio is obtained by ICP test.
[0065] In the present invention, the XRD spectrum of the catalyst was obtained by using the Ultima IV X-ray powder diffractometer produced by Rigaku Corporation of Japan. The voltage was selected as 35 kV, the current was selected as 30 mA, and the scanning speed was 1°·min -1 . When scanning at a small angle, the 2θ angle is 1-5°, and when scanning at a wide angle, the 2θ angle is 5-80°
[0066] In the present invention, a G2F30 transmission electron microscope produced by FEI Company of the United States is used to obtain a TEM photograph of the catalyst. Before the test, the sample to be tested needs to be ground for 1-5 minutes, and then a large amount of ethanol is added to ultrasonically disperse it evenly. The suspension is added dropwise on a copper mesh, and the test can be carried out after the ethanol is completely evaporated.
[0067] In the present invention, the BEL-MAX specific surface and pore size analyzer produced by BELSORP of Japan is used to test the nitrogen adsorption and desorption isotherms of the catalyst at liquid nitrogen temperature, and the total specific surface area and total pore volume are calculated using the BET equation.
[0068] In the present invention, the mechanical strength of the catalyst is tested by using the DLIII intelligent particle strength tester of Dalian Penghui Technology Development Co., Ltd. The length of the tested catalyst is 5 mm and it is placed horizontally on the tester to test the maximum pressure the catalyst withstands when it is broken. After testing the crushing strength of 20 catalysts, the average value is taken.
[0069] In the present invention, the bulk density of the catalyst is measured using a 1000 ml graduated cylinder as the container, and the actual weight of the added catalyst (unit: g) is divided by the actual volume, and the unit is g·cm -3 .
[0070] In the present invention, Kontron Model S-35 ICP-AES analyzer is used to perform ICP testing to obtain silicon-to-aluminum ratio data.
[0071] [Example 1]
[0072] This embodiment is used to synthesize a catalyst for alkylation to produce substituted aromatics. The specific preparation process is as follows: 252 grams of tetraethylammonium hydroxide aqueous solution (concentration of 35wt%), 60 grams of white carbon black, 3.8 grams of pseudo-boehmite (Al2O3 mass content of 70%) and 270 grams of water are mixed evenly, and stirred at 170°C for 5 hours in a closed container to obtain a mixture A1. 120 grams of the mixture A1, 120 grams of silicon powder, 8.5 grams of sodium aluminate (Al2O3 mass content of 40%) and 2.4 grams of pseudo-boehmite (Al2O3 mass content of 70%) are contacted to obtain a mixture B1. B1 is extruded and molded with an appropriate amount of deionized water to obtain a mixture C1 (C1 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-4mm). 3 g of hydrofluoric acid, 300 g of tetraethylammonium hydroxide and 100 g of mixture C1 were treated at 170° C. for 48 hours in a closed space, then washed with deionized water until the pH value was 7.5, dried at 150° C. for 15 hours, and calcined at 550° C. for 6 hours in an air atmosphere to obtain mixture D1. 100 g of mixture D1 and 1000 g of 0.5% hydrochloric acid aqueous solution were treated at 50° C. for 2 hours in a closed space, then the acid solution was poured out, and 1000 g of 20% ammonium sulfate salt solution was added and treated at 50° C. for 2 hours in a closed space, then washed with deionized water until the pH value was 7.5, and dried at 150° C. for 15 hours to obtain mixture E1. Mix 50g of mixture E1 and 500g of an organic base solution with a mass concentration of 10% (the solution contains four organic bases, tetraethylammonium hydroxide, tetra-n-butylammonium hydroxide, di-n-octyldiphenylmethylammonium hydroxide and diphenylmethyldiphenylethylammonium hydroxide, with the mass proportions of the four being 88%, 4%, 4% and 4% respectively) to obtain mixture F1. Mixture F1 is treated at 150°C for 24 hours in a closed space, and then washed with deionized water until the pH value of the solution is 7, dried at 12°C for 24 hours, and calcined at 550°C for 5 hours to obtain catalyst G1.
[0073] The XRD spectrum of catalyst G1 is shown in Figure 1 As shown in the figure, typical diffraction peaks of Beta molecular sieve. Figure 2 As shown, the molecular sieve crystal contains three kinds of nearly spherical cavities with different sizes. The diameter distribution ranges of the circles corresponding to the vertical projections of the three cavities from top to bottom are 10-35nm, 40-52nm and 60-95nm, respectively. The proportions of the three cavities are 38%, 55% and 7%, respectively. Through testing, the total specific surface area of the alkylation aromatics catalyst G1 is 848m 2 ·g -1 , with a total pore volume of 1.2 cm 3 ·g -1 , mechanical strength is 72N / cm, bulk density is 0.52g·cm -3The SiO2 / Al2O3 molar ratio of catalyst G1 was 37.5 as determined by ICP testing.
[0074] [Example 2]
[0075] This embodiment is used to synthesize a catalyst for producing aromatic hydrocarbons by alkylation. The specific preparation process is as follows: 84 grams of tetraethylammonium hydroxide aqueous solution (concentration of 35wt%), 60 grams of white carbon black, 7.6 grams of pseudo-boehmite (Al2O3 mass content of 70%) and 200 grams of water are mixed evenly, and stirred at 130°C for 12 hours in a closed container to obtain a mixture A2. 120 grams of the mixture A2, 150 grams of silicon powder, 17 grams of sodium aluminate (Al2O3 mass content of 40%) and 4.8 grams of pseudo-boehmite (Al2O3 mass content of 70%) are contacted to obtain a mixture B2. B2 is extruded by adding an appropriate amount of deionized water to obtain a mixture C2 (C2 is a four-leaf clover shape with a diameter of 1.8mm and a length of 2-4mm). 1 g of ammonium fluoride, 200 g of tetraethylammonium hydroxide and 100 g of mixture C2 were treated in a closed space at 130° C. for 72 hours, then washed with deionized water until the pH value was 7.5, dried at 160° C. for 15 hours, and calcined at 550° C. in an air atmosphere for 8 hours to obtain mixture D2. 100 g of mixture D2 and 150 g of a 0.5% hydrochloric acid aqueous solution were treated in a closed space at 20° C. for 2 hours, then the acid solution was poured out, and 150 g of a 5% ammonium sulfate salt solution was added and treated in a closed space at 20° C. for 2 hours, then washed with deionized water until the pH value was 7.3, and dried at 120° C. for 24 hours to obtain mixture E2. 50 grams of mixture E2 and 75 grams of organic base solution with a mass concentration of 20% (the solution contains five organic bases of tetraethylammonium hydroxide, tetra-n-pentylammonium hydroxide, tetra-n-octylammonium hydroxide, di-n-heptyldiphenylmethylammonium hydroxide and diphenylmethyldiphenylethylammonium hydroxide, and the mass proportions of the five are 84%, 4%, 4%, 4% and 4% respectively) are mixed uniformly to obtain mixture F2. Mixture F2 is treated at 130° C. for 72 hours in a closed space, and then washed with deionized water until the pH value of the solution is 7, dried at 120° C. for 24 hours, and calcined at 550° C. for 8 hours to obtain alkylation aromatics catalyst G2.
[0076] The XRD spectrum of the alkylation aromatics catalyst G2 has a typical Beta molecular sieve diffraction peak. The molecular sieve crystal contains three kinds of nearly spherical cavities with different size distributions. The diameter distribution ranges of the circles corresponding to the vertical projections of these three cavities from top to bottom are within 10-22nm, 45-50nm and 60-85nm, respectively. The proportions of the three cavities are 35%, 55% and 10%, respectively. Through testing, the total specific surface area of the alkylation ethylbenzene catalyst G2 is 720m 2 ·g -1, the total pore volume is 0.92cm 3 ·g -1 , mechanical strength is 98N / cm, bulk density is 0.58g·cm -3 The SiO2 / Al2O3 molar ratio of the alkylation aromatics catalyst G2 was found to be 18.5 by ICP testing.
[0077] [Example 3]
[0078] This embodiment is used to synthesize a catalyst for producing aromatic hydrocarbons by alkylation. The specific preparation process is as follows: 84.2 grams of tetraethylammonium hydroxide (aqueous solution with a concentration of 35 wt%), 208.3 grams of tetraethyl silicate, 21.25 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 180 grams of water are mixed evenly, and stirred in a closed container at 170° C. for 48 hours to obtain a mixture A3. 120 grams of the mixture A3, 200 grams of silicon powder, 35.4 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 20.2 grams of pseudo-boehmite (with an Al2O3 mass content of 70%) are contacted to obtain a mixture B3. B3 is extruded by adding an appropriate amount of deionized water to obtain a mixture C3 (C3 is cylindrical, with a diameter of 1.7 mm and a length of 2-4 mm). 3 g of ammonium fluorosilicate, 150 g of tetraethylammonium hydroxide and 100 g of mixture C3 were treated at 170° C. for 48 hours in a closed space, then washed with deionized water until the pH value was 7.5, dried at 150° C. for 15 hours, and calcined at 500° C. for 10 hours in an air atmosphere to obtain mixture D3. 100 g of mixture D3 and 1000 g of 0.1% nitric acid aqueous solution were treated at 50° C. for 1 hour in a closed space, then the acid solution was poured out, and 1000 g of 15% ammonium nitrate salt solution was added and treated at 50° C. for 1 hour in a closed space, then washed with deionized water until the pH value was 7.5, and dried at 200° C. for 10 hours to obtain mixture E3. 50 grams of mixture E3 and 500 grams of an organic base solution with a mass concentration of 10% (the solution contains three organic bases, tetraethylammonium hydroxide, di-n-pentyldibenzhydrylammonium hydroxide and tri-n-hexylmonoethylammonium hydroxide, with the mass proportions of the three being 84%, 8% and 8% respectively) are mixed evenly to obtain a mixture F3. The mixture F3 is treated at 150° C. for 25 hours in a closed space, and then washed with deionized water until the pH value of the solution is 7, dried at 120° C. for 24 hours, and calcined at 600° C. for 5 hours to obtain an alkylation catalyst for producing aromatics G3.
[0079] The XRD spectrum of the alkylation aromatics catalyst G3 has a typical Beta molecular sieve diffraction peak. The molecular sieve crystal contains three kinds of nearly spherical cavities with different size distributions. The diameter distribution ranges of the circles corresponding to the vertical projections of these three cavities from top to bottom are respectively within 22-30nm, 45-50nm and 75-90nm. The proportions of the three cavities are 20%, 75% and 5% respectively. Through testing, the total specific surface area of the alkylation ethylbenzene catalyst G3 is 830m 2 ·g -1 , with a total pore volume of 1.2 cm 3 ·g -1 , mechanical strength is 78N / cm, bulk density is 0.52g·cm -3 The SiO2 / Al2O3 molar ratio of the alkylation aromatics catalyst G3 was 13.9 as determined by ICP testing.
[0080] [Example 4]
[0081] This embodiment is used to synthesize a catalyst for producing aromatic hydrocarbons by alkylation. The specific preparation process is as follows: 84.2 grams of tetraethylammonium hydroxide (aqueous solution with a concentration of 35 wt%), 208.3 grams of tetraethyl silicate, 21.25 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 180 grams of water are mixed evenly, and stirred at 130° C. for 12 hours in a closed container to obtain a mixture A4. 120 grams of the mixture A4, 200 grams of silicon powder, 35.4 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 20.2 grams of pseudo-boehmite (with an Al2O3 mass content of 70%) are contacted to obtain a mixture B4. B4 is extruded by adding an appropriate amount of deionized water to obtain a mixture C4 (C4 is cylindrical, with a diameter of 1.8 mm and a length of 2-3 mm). 1 g of ammonium fluoride, 150 g of tetraethylammonium hydroxide and 100 g of mixture C4 were treated at 130° C. for 72 hours in a closed space, then washed with deionized water until the pH value was 7.5, dried at 150° C. for 15 hours, and calcined at 550° C. for 6 hours in an air atmosphere to obtain mixture D4. 100 g of mixture D4 and 150 g of 0.4% nitric acid aqueous solution were treated at 20° C. for 1 hour in a closed space, then the acid solution was poured out, and 150 g of 5% ammonium nitrate salt solution was added and treated at 20° C. for 1 hour in a closed space, then washed with deionized water until the pH value was 7.5, and dried at 150° C. for 15 hours to obtain mixture E4. 50 g of mixture E4 and 400 g of an organic base solution with a mass concentration of 18% (the solution contains three organic bases, tetraethylammonium hydroxide, di-n-heptyldibenzhydrylammonium hydroxide and tri-n-hexylmonoethylammonium hydroxide, with the mass proportions of the three being 84%, 8% and 8% respectively) are mixed evenly to obtain mixture F4. Mixture F4 is treated at 130° C. for 72 hours in a closed space, then washed with deionized water until the pH value of the solution is 7, dried at 120° C. for 24 hours, and calcined at 580° C. for 5 hours to obtain alkylation aromatics catalyst G4.
[0082] The XRD spectrum of the alkylation aromatics catalyst G4 has a typical Beta molecular sieve diffraction peak. The molecular sieve crystal contains three kinds of nearly spherical cavities with different size distributions. The diameter distribution ranges of the circles corresponding to the vertical projections of these three cavities from top to bottom are respectively within 24-30nm, 42-50nm and 75-90nm. The proportions of the three cavities are 38%, 56% and 6% respectively. Through testing, the total specific surface area of the alkylation ethylbenzene catalyst G4 is 810m 2 ·g -1 , with a total pore volume of 1.1 cm 3 ·g -1 , mechanical strength is 89N / cm, bulk density is 0.53g·cm -3The SiO2 / Al2O3 molar ratio of the alkylation aromatics catalyst G4 was found to be 14.5 by ICP testing.
[0083] [Example 5]
[0084] This embodiment is used to synthesize a catalyst for producing aromatic hydrocarbons by alkylation. The specific preparation process is as follows: 90 grams of tetraethylammonium hydroxide (aqueous solution with a concentration of 35 wt%), 208.3 grams of tetraethyl silicate, 21.25 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 180 grams of water are mixed evenly, and stirred in a closed container at 130° C. for 12 hours to obtain a mixture A5. 120 grams of the mixture A5, 200 grams of silicon powder, 35.4 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 20.2 grams of pseudo-boehmite (with an Al2O3 mass content of 70%) are contacted to obtain a mixture B5. B5 is extruded by adding an appropriate amount of deionized water to obtain a mixture C5 (C5 is gear-shaped with a diameter of 1.8 mm and a length of 2-3 mm). 1 g of ammonium fluoride, 150 g of tetraethylammonium hydroxide and 100 g of mixture C5 were treated at 130° C. for 72 hours in a closed space, then washed with deionized water until the pH value was 7.5, dried at 150° C. for 15 hours, and calcined at 550° C. for 6 hours in an air atmosphere to obtain mixture D5. 100 g of mixture D5 and 150 g of a 0.1% hydrochloric acid aqueous solution were treated at 20° C. for 1 hour in a closed space, then the acid solution was poured out, and 150 g of a 5% ammonium nitrate salt solution was added and treated at 20° C. for 1 hour in a closed space, then washed with deionized water until the pH value was 7.5, and dried at 150° C. for 15 hours to obtain mixture E5. 50 g of the mixture E5 and 150 g of an organic base solution with a mass concentration of 20% (the solution contains three organic bases, tetraethylammonium hydroxide, di-n-octyldibenzhydrylammonium hydroxide and tri-n-hexylmonoethylammonium hydroxide, with the mass proportions of the three being 88%, 5% and 7%, respectively) are mixed evenly to obtain a mixture F5. The mixture F5 is treated at 140° C. for 60 hours in a closed space, and then washed with deionized water until the pH value of the solution is 7, dried at 120° C. for 24 hours, and calcined at 580° C. for 5 hours to obtain an alkylation aromatics catalyst G5.
[0085] The XRD spectrum of the alkylation aromatics catalyst G5 has a typical Beta molecular sieve diffraction peak. The molecular sieve crystal contains three kinds of nearly spherical cavities with different size distributions. The diameter distribution ranges of the circles corresponding to the vertical projections of these three cavities from top to bottom are 16-28nm, 42-50nm and 62-85nm, respectively. The proportions of the three cavities are 32%, 60% and 8%, respectively. Through testing, the total specific surface area of the alkylation aromatics catalyst G5 is 780m 2 ·g -1, with a total pore volume of 1.0 cm 3 ·g -1 , mechanical strength is 95N / cm, bulk density is 0.54g·cm -3 The SiO2 / Al2O3 molar ratio of the alkylation catalyst G5 to ethylbenzene was found to be 13.2 by ICP test.
[0086] [Example 6]
[0087] This embodiment is used to synthesize a catalyst for producing aromatic hydrocarbons by alkylation. The specific preparation process is as follows: 100 grams of tetraethylammonium hydroxide (aqueous solution with a concentration of 35 wt%), 208.3 grams of tetraethyl silicate, 21.25 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 180 grams of water are mixed evenly, and stirred at 130° C. for 12 hours in a sealed container to obtain a mixture A6. 120 grams of the mixture A6, 200 grams of silicon powder, 35.4 grams of sodium aluminate (with an Al2O3 mass content of 40%) and 20.2 grams of pseudo-boehmite (with an Al2O3 mass content of 70%) are contacted to obtain a mixture B6. B6 is extruded by adding an appropriate amount of deionized water to obtain a mixture C6 (C6 is a clover-shaped, with a diameter of 2.1 mm and a length of 2-3 mm). 1 g of ammonium fluoride, 150 g of tetraethylammonium hydroxide and 100 g of mixture C6 were treated at 160° C. for 60 hours in a closed space, then washed with deionized water until the pH value was 7.5, dried at 150° C. for 15 hours, and calcined at 550° C. in an air atmosphere for 6 hours to obtain mixture D6. 100 g of mixture D6 and 300 g of 0.4% sulfuric acid aqueous solution were treated at 20° C. for 1.5 hours in a closed space, then the acid solution was poured out, and 300 g of 5% ammonium nitrate salt solution was added and treated at 20° C. for 1.5 hours in a closed space, then washed with deionized water until the pH value was 7.5, and dried at 150° C. for 15 hours to obtain mixture E6. 50g of mixture E6 and 300g of an organic base solution with a mass concentration of 14% (the solution contains three organic bases, tetraethylammonium hydroxide, di-n-pentyldibenzhydrylammonium hydroxide and tri-n-hexylmonoethylammonium hydroxide, with the mass proportions of the three being 84%, 8% and 8% respectively) are mixed evenly to obtain mixture F6. Mixture F6 is treated at 130°C in a closed space for 72 hours, then washed with deionized water until the pH value of the solution is 7, dried at 120°C for 24 hours and calcined at 550°C for 5 hours to obtain alkylation aromatics catalyst G6.
[0088] The XRD spectrum of the alkylation aromatics catalyst G6 has a typical Beta molecular sieve diffraction peak. The molecular sieve crystal contains three kinds of nearly spherical cavities with different size distributions. The diameter distribution ranges of the circles corresponding to the vertical projections of these three cavities from top to bottom are 12-28nm, 45-50nm and 60-90nm, respectively. The proportions of the three cavities are 33%, 60% and 7%, respectively. According to the test, the total specific surface area of the alkylation ethylbenzene catalyst G6 is 780m 2 ·g -1 , the total pore volume is 0.95cm 3 ·g -1 , mechanical strength is 100N / cm, bulk density is 0.57g·cm -3 The SiO2 / Al2O3 molar ratio of the alkylation aromatics catalyst G6 was found to be 13.2 by ICP testing.
[0089] [Comparative Example 1]
[0090] Compared with Example 1, only mixture D was not treated with an acid solution, and the rest was the same. The specific preparation process of the catalyst is as follows: 252 grams of tetraethylammonium hydroxide aqueous solution (concentration of 35wt%), 60 grams of white carbon black, 3.8 grams of pseudo-boehmite (Al2O3 mass content of 70%) and 270 grams of water were mixed evenly, and stirred at 170°C for 5 hours in a closed container to obtain a mixture a1. 120 grams of mixture a1, 120 grams of silicon powder, 8.5 grams of sodium aluminate (Al2O3 mass content of 40%) and 2.4 grams of pseudo-boehmite (Al2O3 mass content of 70%) were contacted to obtain a mixture b1. Add an appropriate amount of deionized water to b1 and extrude it to obtain a mixture c1 (c1 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-4mm). 3 grams of hydrofluoric acid, 300 grams of tetraethylammonium hydroxide and 100 grams of mixture c1 were treated at 170°C in a closed space for 48 hours, then washed with deionized water until the pH value was 7.5, dried at 150°C for 15 hours, and roasted at 550°C in an air atmosphere for 6 hours to obtain mixture d1. 100 grams of mixture d1 and 1000 grams of ammonium sulfate salt solution with a mass concentration of 20% were treated at 50°C in a closed space for 2 hours, then washed with deionized water until the pH value was 7.5, and dried at 150°C for 15 hours to obtain mixture e1. 50 grams of mixture e1 and 500 grams of organic base solution with a mass concentration of 10% (the solution contains four organic bases of tetraethylammonium hydroxide, tetra-n-butylammonium hydroxide, di-n-octyldiphenylmethylammonium hydroxide and diphenylmethyldiphenylethylammonium hydroxide, and the mass proportions of the four are 88%, 4%, 4% and 4% respectively) were mixed uniformly to obtain mixture f1. The mixture f1 was treated at 150°C for 24 hours in a closed space, then washed with deionized water until the pH value of the solution was 7, dried at 12°C for 24 hours, and calcined at 550°C for 5 hours to obtain the catalyst g1.
[0091] The TEM image of catalyst g1 is shown in Figure 3 As shown in the figure, there is no obvious cavity inside the molecular sieve crystal, and the total specific surface area of catalyst g1 is 570m 2 ·g -1 , with a total pore volume of 0.35 cm 3 ·g -1 , mechanical strength is 128N / cm, bulk density is 0.62g·cm -3 The SiO2 / Al2O3 molar ratio of catalyst g1 was 38.2 as determined by ICP testing.
[0092] [Comparative Example 2]
[0093] Compared with Example 1, only tetraethylammonium hydroxide is used as the organic base, and the rest is the same. 252 grams of tetraethylammonium hydroxide aqueous solution (concentration is 35wt%), 60 grams of white carbon black, 3.8 grams of pseudo-boehmite (Al2O3 mass content is 70%) and 270 grams of water are mixed evenly, and stirred at 170°C for 5 hours in a closed container to obtain mixture a2. 120 grams of mixture a2, 120 grams of silicon powder, 8.5 grams of sodium aluminate (Al2O3 mass content is 40%) and 2.4 grams of pseudo-boehmite (Al2O3 mass content is 70%) are contacted to obtain mixture b2. B2 is extruded by adding an appropriate amount of deionized water to obtain mixture c2 (c2 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-4mm). 3 grams of hydrofluoric acid, 300 grams of tetraethylammonium hydroxide and 100 grams of mixture c2 were treated at 170°C for 48 hours in a closed space, then washed with deionized water until the pH value was 7.5, dried at 150°C for 15 hours, and roasted at 550°C in an air atmosphere for 6 hours to obtain mixture d2. 100 grams of mixture d2 and 1000 grams of 0.5% hydrochloric acid aqueous solution were treated at 50°C for 2 hours in a closed space, then the acid solution was poured out, and 1000 grams of 20% ammonium sulfate salt solution was added and treated at 50°C for 2 hours in a closed space, then washed with deionized water until the pH value was 7.5, and dried at 150°C for 15 hours to obtain mixture e2. 50 grams of mixture e2 and 500 grams of 10% organic base solution (containing only tetraethylammonium hydroxide in the solution) were mixed evenly to obtain mixture f2. The mixture f2 was treated at 150°C for 24 hours in a closed space, and then washed with deionized water until the pH value of the solution was 7, dried at 12°C for 24 hours, and calcined at 550°C for 5 hours to obtain the catalyst g2.
[0094] The XRD spectrum of catalyst g2 is shown in Figure 4 As shown in the figure, typical diffraction peaks of Beta molecular sieve. Figure 5 As shown in Figure 2, the internal cavity of the molecular sieve crystal is irregular in shape, and the diameter of the cavity is more than 160nm. Through testing, the total specific surface area of catalyst G2 is 586m 2 ·g -1 , with a total pore volume of 1.35 cm 3 ·g -1 , mechanical strength is 57N / cm, bulk density is 0.49g·cm -3 The SiO2 / Al2O3 molar ratio of catalyst H2 was 37.6 as determined by ICP testing.
[0095] [Example 7]
[0096] Catalysts G1-G6 and g1-g2 prepared in Examples 1-6 and Comparative Examples 1-2 were respectively applied to the alkylation of ethylbenzene and isobutylene to produce ethyl tert-butylbenzene at a reaction temperature of 140°C, a pressure of 1.5 MPa, and an isobutylene mass space velocity of 4.5 h -1 , the isobutylene conversion rate was tested under the condition that the molar ratio of ethylbenzene to isobutylene was 2.0. The test results are shown in Table 1 below.
[0097] Table 1 Alkylation of ethylbenzene and isobutylene to produce ethyl tert-butylbenzene
[0098] Catalyst No. Isobutylene conversion, wt% G1 98.0 G2 97.5 G3 98.3 G4 96.4 G5 94.5 G6 95.7 g1 79.6 g2 86.1
[0099] [Example 8]
[0100] Catalysts G1-G6 and g1-g2 prepared in Examples 1-6 and Comparative Examples 1-2 were respectively applied to the alkylation of benzene and ethylene to produce ethylbenzene at a reaction temperature of 210°C, a pressure of 3.5 MPa, and an ethylene mass space velocity of 1.0 h -1 , under the condition that the molar ratio of benzene to ethylene was 1.5, the ethylene conversion rate and the ethyl selectivity in the alkylation product were tested. The test results are shown in Table 2 below.
[0101] Table 2 Alkylation of benzene and ethylene to produce ethylbenzene
[0102]
[0103] [Example 9]
[0104] The catalysts G1-G6 and g1-g2 prepared in Examples 1-6 and Comparative Examples 1-2 were tested for their one-way life in the alkylation of benzene and ethylene to produce ethylbenzene under ultra-high ethylene mass space velocity reaction conditions. The specific test conditions are as follows: reaction temperature 220°C, pressure 3.5MPa, ethylene mass space velocity 6h -1 , the molar ratio of benzene to ethylene is 1.5, and the one-way life refers to the time from the start of the reaction to the time when the ethylene conversion rate drops to 40% of the initial conversion rate. The test results are shown in Table 3 below. Under ultra-high ethylene space velocity reaction conditions, the one-way life of G1-G6 is significantly longer than that of g1-g2.
[0105] Table 3 Single-pass life test results of catalysts under ultra-high space velocity reaction conditions
[0106] Catalyst No. One-way life, h G1 520 G2 505 G3 498 G4 485 G5 505 G6 513 g1 268 g2 345
[0107] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for producing substituted aromatics by alkylation, characterized in that: Reaction raw materials aromatic hydrocarbons and olefins are contacted with a molecular sieve catalyst to generate substituted aromatic hydrocarbons; the molecular sieve crystals in the molecular sieve catalyst contain three kinds of nearly spherical cavities with size distributions, and the diameter distribution ranges of the circles corresponding to the vertical projections of the three cavities from top to bottom are respectively within 5-35 nm, 40-55 nm and 60-100 nm; the proportions of the numbers of the three cavities are 15-45%, 45-75% and 5-10% respectively; the molecular sieve is a silicon-aluminum molecular sieve with a twelve-membered ring pore structure; the silicon-aluminum molecular sieve is a binder-free molecular sieve.
2. The method according to claim 1, characterized in that: The reaction temperature is 50-260 °C, the reaction pressure is 0.1-5.0 MPa, and the olefin mass space velocity is 0.1-20.0 h -1 , the molar ratio of aromatics to olefins is 1-30.
3. A catalyst for producing substituted aromatics by alkylation, characterized in that: The catalyst is a molecular sieve catalyst, and the molecular sieve crystals in the catalyst contain three kinds of nearly spherical cavities with size distributions. The diameter distribution ranges of the circles corresponding to the vertical projections of the three cavities from top to bottom are respectively within 5-35 nm, 40-55 nm and 60-100 nm; the proportions of the number of the three cavities are 15-45%, 45-75% and 5-10% respectively; the molecular sieve is a silicon-aluminum molecular sieve with a twelve-membered ring pore structure; the silicon-aluminum molecular sieve is a binder-free molecular sieve.
4. The catalyst according to claim 3, characterized in that The molecular sieve is Beta molecular sieve.
5. The catalyst according to claim 3, characterized in that The total specific surface area of the catalyst is 680-950 m 2 ·g -1 ; Total pore volume is 0.8-1.3 cm 3 ·g -1 ; Mechanical strength is 70-100 N / cm; Bulk density is 0.50-0.60 g·cm -3 .
6. The catalyst according to claim 3, characterized in that The SiO2 / Al2O3 molar ratio of the catalyst is 10-100.
7. A method for preparing the catalyst according to any one of claims 3 to 6, comprising the steps of: (a) treating the molecular sieve with an acid and an ammonium salt solution to obtain a mixture E; (b) Mixture E is contacted with a mixed organic base to obtain mixture F, and mixture F is treated at 120-170° C. for 24-96 hours, and then washed, dried and calcined to obtain a molecular sieve catalyst.
8. The preparation method according to claim 7, characterized in that: The acid used in the acid treatment in step (a) is one or more of hydrochloric acid, sulfuric acid, and nitric acid, and the acid used in the acid treatment is an aqueous solution of the acid with a mass concentration of 0.1-1.0%.
9. The preparation method according to claim 7, characterized in that: In step (a), the ammonium salt is one or more of ammonium chloride, ammonium nitrate and ammonium sulfate, and the ammonium salt solution is an aqueous solution with a mass concentration of 3-30%.
10. The preparation method according to claim 7, characterized in that: The mixed organic base in step (b) is a mixed organic base aqueous solution, and its mass concentration is 8%-25%; the mass ratio of the mixed organic base aqueous solution to the mixture E is (1.2-15):
1.
11. The preparation method according to claim 7, characterized in that: The mixed organic base in step (b) is a mixed alkali aqueous solution of tetraethylammonium hydroxide and at least two other different quaternary ammonium bases, and the structural formula of the other quaternary ammonium base is: wherein R1, R2, R3 and R4 are each independently selected from n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, benzyl or phenethyl.
12. The preparation method according to claim 11, characterized in that: The mass ratio of tetraethylammonium hydroxide to the total amount of other quaternary ammonium bases is (5-8):
1.
13. The preparation method according to claim 12, characterized in that: The mass proportion of each quaternary ammonium base in other quaternary ammonium bases is 20%-60%.
Citation Information
Patent Citations
A hollow hierarchical porous Beta molecular sieve, its preparation method and application
CN109534358B
Alkylation reaction method
CN103964994A
Aromatization catalyst as well as preparation method and application thereof
CN111151292A